2020
DOI: 10.3390/ani10081292
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Black Soldier Fly and Yellow Mealworm Fats and Their Impact on Gut Microbiota of Growing Rabbits

Abstract: This study aimed to evaluate the in vitro antimicrobial activities of two types of insect fats extracted from black soldier fly larvae (HI, Hermetia illucens L.) and yellow mealworm larvae (TM, Tenebrio molitor L.) and their effects as dietary replacement of soybean oil (S) on cecal fermentation pattern, and fecal and cecal microbiota in rabbits. A total of 120 weaned rabbits were randomly allotted to three dietary treatments (40 rabbits/group) —a control diet (C diet) containing 1.5% of S and two experimental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 71 publications
2
31
0
1
Order By: Relevance
“…The relative abundance of Subdoligranulum and Ruminococcus_2 has also been found to differ in different broiler chicken lines from the same poultry farm [25]. Additionally, Ruminococcus species have been reported to improve the immune response in rabbits [26].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Subdoligranulum and Ruminococcus_2 has also been found to differ in different broiler chicken lines from the same poultry farm [25]. Additionally, Ruminococcus species have been reported to improve the immune response in rabbits [26].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in this first phase, the weight of the chicken increases the initial weight up to four times. This fact determines its subsequent growth [ 5 , 10 ]. That is why the contribution of nutrients of high biological and nutritional quality, such as insects, are key to the correct productive development of the chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary ingestion of HI and TM fats in substitution of 50 and 100% of soybean oil in the diets of growing rabbits did not influence the gut morphometry or alter the liver functions (Gasco et al, 2019b), although a positive effect on microbiota has been suggested (Dabbou et al, 2020). Indeed, an increase in the relative abundance of Bacteroides, Clostridium, Akkermansia and Ruminococcus has been observed.…”
Section: Pigs and Rabbitsmentioning
confidence: 86%
“…Akkermansia has been indicated as being able to degrade the mucin in the intestine, with a consequent production of SCFAs and consequent positive effects on gut health. Ruminococcus are also butyrate producing bacteria that contribute to the positive effect on the caecal microbiota of rabbits (Dabbou et al, 2020).…”
Section: Pigs and Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation